The Just War Tradition and the Moral Reality of War: A Principled Approach to Moral Exceptionalism - Ford, Shannon (2019)
The conventional view of just war thinking holds that militaries operate under “special” moral rules in war. It treats military combatants according to a moral standard different from the everyday standard. Soldiers are morally permitted to kill enemy soldiers, and vice versa, because both parties hold the status of military combatants. This “moral exceptionalism” gives the military special permissions to kill enemy combatants in war. Military exceptionalism here refers to the view that military combatants in active theatres of war are not bound by the same moral rules about killing that apply to an ordinary person in peacetime. Michael Walzer refers to this as the adaption of ordinary morality to the “moral reality of war.” Michael Walzer was summarising the long history of thinking in the just war tradition when he said that wars are not the moral responsibility of soldiers. That is, the “war itself isn’t a relation between persons but between political entities and their human instruments.” This understanding of the moral exceptionalism of military combatancy in war has, however, been critiqued by the Revisionist movement. In particular, Jeff McMahan argues that the establishment of political relations among a group of people does not confer on them an exceptional right to harm or kill others, when the harming or killing would be impermissible in the absence of that political relationship. Hence, he disagrees with the notion that a military’s use of lethal force in war is morally exceptional in the way that conventional just war presumes. In this paper, I describe the way in which the just war tradition relies on moral exceptionalism to justify killing in war. Next I outline the Revisionist challenge to this notion. Then, I outline the reasons why we should conclude that wartime killing is morally exceptional.